Carbene-catalyzed LUMO activation of alkyne esters for access to functional pyridines - Mou, Chengli (2020)
A carbene-catalyzed LUMO activation of a,b-unsaturated alkyne esters is reported. This catalytic process allows for effective reactions of alkyne esters with enamides to synthesize functional pyridines via simple protocols. A previously unexplored unsaturated alkyne acyl azolium intermediate is involved in the key step of the reaction.